Evaluating the ability of economic models of diabetes to simulate new cardiovascular outcomes trials: A report on the ninth mount hood diabetes challenge - Si, L; Willis, MS; Asseburg, C; Nilsson, A; Tew, M; Clarke, PM; Lamotte, M; Ramos, M; Shao, H; Shi, L; Zhang, P; McEwan, P; et al. (Elsevier, 2020)
Objectives: The cardiovascular outcomes challenge examined the predictive accuracy of 10 diabetes models in estimating hard outcomes in 2 recent cardiovascular outcomes trials (CVOTs) and whether recalibration can be used to improve replication.